Education of the Affective Ideal in Contexts of Cultural Diversity: BIBLIOMETRIC and Thematic Analysis (2006-2021) - Carrasco, Ingrid Bravo; Mella, Enrique Riquelme; Saldivia, Ximena Gutiérrez; Vilugrón, Gerardo Fuentes (International Journal of Membrane Science and Technology, 2023)
Emotional education has grown exponentially in the last decade, although outlining an emotional regulation from parameters of majority cultural groups that leaves aside the socialization of emotion from an affective ideal- or the expected behaviour on the emotional plane that considers cultural differences and education minority group family members. This study is to analyse research about the affective ideal in contexts of cultural diversity to contribute to it understanding in education, through a review of documents published in the Web of Sciences, Scopus, and APA PsycNet databases, in the diachronic period 2006-2021. The need for an emotional education that recognizes the affective ideal of the cultures shared in a territory is discussed. It is concluded that there is an incipient investigation of cultural mediatization on the affective ideal in contexts of sociocultural diversity, and little research in the educational plane. This should be preferred in Latin America, marked by models of monocultural emotional education models, which in culturally diverse educational settings, translates into discrimination and racism.